Checklist of Lycopodiaceae in Vietnam with three new records and one lectotypification - Lu, Ngan Thi; Duy, Hung Nguyen; Sennikov, Alexander N.; Averyanov, Leonid V.; Do, Truong Van; Kuznetsov, Andrey N.; Kuznetsova, Svetlana P.; Nuraliev, Maxim S. (Phytotaxa, 2020)
An updated checklist of the family Lycopodiaceae in Vietnam is provided. The checklist is based on the most recent taxonomic delimitation of this family. It comprises three subfamilies, six genera and 20 species. Three species, Huperzia nanlingensis, Phlegmariurus henryi and Phlegmariurus tetrastichus, are reported from Vietnam for the first time, which is mainly a result of floristic exploration of the country during the last 15 years. Detailed descriptions and photographs are provided for the newly recorded species, as well as a map showing their distribution in Vietnam. Taxonomy of these and related species is briefly discussed. Type material of P. tetrastichus was analyzed and a specimen from G (G00349152) was designated as a lectotype. It was demonstrated that the combination Huperzia tetrasticha has never been validly published.